Analisis Sistem Pengendalian Internal Atas Penggajian Aparatur Sipil Negara Pada Kantor Sekretariat DPRD Kabupaten Batang Hari - Fauziah Fauziah; Neng Setiawati; Anggri Anggri (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2020)
The Batang Hari DPRD Secretariat Office has an internal control system for ASN payrolls which is shown from the procedures and the existence of an authorization system carried out by the Secretariat. This analysis also aims to determine whether the implementation of control is effective, efficient, and accountable. The method in this research is descriptive qualitative in the form of depicting the object under study which only explains in accordance with reality so that the research objectives can be answered, and the deductive method is an approach that uses logic to draw one or more conclusions based on a set of premises given. Internal Control System At the Secretariat Office of the Batang Hari DPRD, the Secretariat of the Batang Hari DPRD makes efforts - Documents are included in the State assets. - Realizing the importance of the principles of the Internal Control System for an agency, the Batang Hari DPRD Secretariat Office carries out a process of performance review, human resource development, physical control of assets, determination and review of performance indicators and measures, separation of functions, authorization of transactions and events important, accurate and timely records, restriction of access to resources and their records, accountability to resources and their records and good documentation, which according to the Author is in accordance with Principles of the Internal Control System itself. -Verifying the reliability of financial reporting data for each activity directly and complying with the legal basis governing it, analyzing based on risk management in special meetings of the finance department, and ensuring the confidentiality of each data through segregation of duties of each staff in the organizational structure are efforts made by the Office Batang Hari DPRD Secretariat. Procedure for Remuneration of State Civil Servants at the Secretariat Office of the Batang Hari DPRD. The civil servant payroll system implemented at the Batang Hari DPRD Secretariat Office - Salary Disbursement Flow prepared by Salary Master Form (FMG), Salary List, Payment Request Letter (SPP), Payment Order (SPM), Fund Disbursement Order (SP2D) and Disbursement of Salaries.